Bootsrap 3 and jQuery and bugs which are related with mobile version of websites - Topol, Vladyslav; Kovalova, Olena (My University, 2020)
Web-development is one of the most popular spheres in the world of IT. A lot of Front-End developers, who work on client`s part of websites, deal with a big amount of bugs. A lot of bugs are related with developing mobile version of websites. When developers create web-sites using framework Bootstrap 3 and jQuery library they have to check how mobile version of website works. These technologies are quite powerful but sometimes mobile version of webpages doesn`t work correctly and developer have to work on it. Веб-розробка - одна з найпопулярніших сфер ІТ у світі. Багато розробників Front-End, які працюють на клієнтській частині веб-сайтів, стикаються з великою кількістю помилок. Дуже багато помилок пов’язано з розробкою мобільної версії веб-сайтів. Коли розробники створюють веб-сайти за допомогою бібліотеки Framework Bootstrap 3 та jQuery, вони повинні перевірити, як працює мобільна версія веб-сайту. Ці технології є досить потужними, але іноді мобільна версія веб-сторінок не працює належним чином, і розробникам доводиться працювати над нею.
Keywords: кафедра ділової іноземної мови та міжнародної комунікації; веб-сайт; мобільна версія